2011
DOI: 10.1007/s12264-011-1531-5
|View full text |Cite
|
Sign up to set email alerts
|

Increased basal plasma brain-derived neurotrophic factor levels in sprint runners

Abstract: Objective Exercise is known to enhance circulating brain-derived neurotrophic factor (BDNF) levels in healthy humans. BDNF changes have been measured in endurance but not in strength exercise. The present study aimed to investigate whether anaerobic activity such as sprinting differentially alters basal plasma BDNF concentration. Methods Brazilian sprinters (100 m) at either the international (Olympics and Outdoor World Championships) (n = 14) or the domestic level (n = 8), and sedentary subjects (n = 15), wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
0
14
2
Order By: Relevance
“…All these articles were published within the last 5 years, suggesting that this is an emerging area of interest. Two studies reported that BDNF was higher in active sportsmen compared with sedentary individuals (Zoladz et al, 2008;Correia et al, 2011), whereas Nofuji et al (2008 showed the opposite results. Two studies failed to observe the significant association (Floel et al, 2010;Winker et al, 2010).…”
Section: The Association Between Physical Activity and Bdnfmentioning
confidence: 99%
See 3 more Smart Citations
“…All these articles were published within the last 5 years, suggesting that this is an emerging area of interest. Two studies reported that BDNF was higher in active sportsmen compared with sedentary individuals (Zoladz et al, 2008;Correia et al, 2011), whereas Nofuji et al (2008 showed the opposite results. Two studies failed to observe the significant association (Floel et al, 2010;Winker et al, 2010).…”
Section: The Association Between Physical Activity and Bdnfmentioning
confidence: 99%
“…Results from observational studies Table 4 summarizes the observational studies investigating the relationship between peripheral BDNF concentrations and habitual physical activity or CRF. Seven studies have looked into the association between physical activity and BDNF (Chan et al, 2008;Nofuji et al, 2008;Zoladz et al, 2008;Currie et al, 2009;Floel et al, 2010;Winker et al, 2010;Correia et al, 2011). Only one study used objective measure of physical activity (Nofuji et al, 2008).…”
Section: Effects Of Chronic Aerobic Exercise On Bdnfmentioning
confidence: 99%
See 2 more Smart Citations
“…While resistance training is a recognised strategy for slowing or preventing the age-related loss of skeletal muscle mass and function [60], exercise and physical activity are recognised as effective strategies for treating depression and anxiety [61, 62, 63•] and reducing the risk for new onset of these disorders [59, 64•]. Contracting skeletal muscle produces BDNF [65], and exercise has been shown to enhance circulating BDNF in a range of diverse settings such as during moderate exercise in patients with multiple sclerosis [66], endurance training in healthy young men [67] and in sprint athletes [68]. Insulin-like growth factor-1 (IGF-1) is one of the factors involved in the expression of BDNF; it is increased after exercise and has neurological effects [69] as well as modulating skeletal muscle growth and atrophy [70].…”
Section: Sarcopenia Mood and Anxiety: What Common Role Does Lifestylmentioning
confidence: 99%